Anak Laki Laki Menjadi Wali Nikah Ibunya Menurut Imam Ibnu Qudamah Dan Imam An-Nawawi - Muhammad Imam Muarif Irsa Ginting; Ahmad Zuhri (Bahasa Indonesia, 2026)
This research aims to analyze sons being guardians of their mother's marriage according to Imam Ibnu Qudamah and Imam An-Nawawi, as well as determining which opinion is the most diligent between the two. This research uses qualitative methods with a normative-comparative approach. The type of research used is library research (library research). Data obtained through a study of primary sources in the form of the al-Mughni book by Imam Ibnu Qudamah and al-Majmu' Syarah al-Muhadzdzab by Imam An-Nawawi, as well as secondary sources in the form of fiqh books, journals and other literature. The data that has been collected is then processed through several stages, namely checking the data (editing), and systematizing the data (systematizing), then analyzed qualitatively using a deductive thinking approach in order to obtain objective conclusions and be able to answer research problems. Imam Ibnu Qudamah is of the opinion that a son is allowed to be his mother's marriage guardian because he is one of the closest people to the woman, as long as there is no other family guardian who has more rights. Meanwhile, Imam An-Nawawi is of the opinion that a son cannot be his biological mother's guardian in marriage because the guardianship is from the father, and a son is not included in the category of ashābah for a woman in the context of marital guardianship